Quality Governance Design Good University Govarnance In The Education Sector: a Literature Review of Concepts Performance Models and Audit Practices From a Risk Management Perspective - Rusdi, M; Sartika, Delita; Putra, Iwan; Sari, Nurmala (CV. AFDIFAL MAJU BERKAH, 2023)
This research outlines the research methodology used in a literature review on the Quality Governance Design of Good University Governance (GUG) in the education sector, with a focus on the GUG concept, performance models, and audit practices from a risk management perspective. The GUG concept is a vital framework for enhancing the quality and effectiveness of higher education institutions such as universities, with principles of transparency, accountability, participation, and ethics as its core components. This concept also emphasizes the importance of innovative ideas and the leadership capabilities of university leaders in facing global changes. Furthermore, this research discusses relevant performance models, including the Balanced Scorecard (BSC) and Key Performance Indicators (KPIs), which assist universities in measuring their performance through financial, customer, internal process, and growth and learning perspectives. These models help universities become more focused, transparent, and accountable in their governance. Audit practices, both internal and external, are also essential elements in higher education risk management. Internal audits help identify operational, financial, and reputational risks, while external audits ensure compliance with accreditation standards. Audit practices help universities manage risks efficiently and strengthen transparency and accountability in educational governance. This research also illustrates the integration of the GUG concept in higher education, including internal and external quality assurance, program accreditation, and sustainable quality improvement. Previous research indicates that many factors influence the quality of university governance, including government influence, leadership, and quality assurance priorities.